IMPLEMENTASI PENDIDIKAN POLITIK DALAM MEMBENTUK KARAKTER KEPEMIMPINAN LINTAS BUDAYA PADA GENERASI MUDA DEMI MEWUJUDKAN BUDAYA POLITIK PANCASILA (Studi Deskriptif terhadap Organisasi Kepemudaan Gerakan Pemuda Ansor Jawa Barat) - Sanusi, Aris Riswandi; Darmawan, Cecep (JURNAL PENDIDIKAN ILMU SOSIAL, 2016)
The young generation is an essential element in a state life. The role of youth, as contained in Law of the Republic of Indonesia No. 40 Year 2009 on Youth that says "youths play an active role as a moral force, social control, and agents of change in all aspects of national development". However, the reality of the situation is that there has been a moral degradation and the decreasing of cross-cultural leadership character in the younger generation. Political education as what Ansor PW GP of West Java implemented is one of many attempts to form a cross-cultural leadership character in young generation in order to create Pancasila political culture.Keywords: political education, cross-cultural leadership, Pancasila political culture, Ansor PW GP of West Java.